Infection complications after lymphodepletion and dosing of chimeric antigen receptor T (CAR-T) cell therapy in patients with relapsed/refractory acute lymphoblastic leukemia or B cell non-Hodgkin lymphoma - Korell, Felix; Schubert, Maria-Luisa; Sauer, Tim; Schmitt, Anita; Derigs, Patrick; Weber, Tim; Schnitzler, Paul; Müller-Tidow, Carsten; Dreger, Peter; Schmitt, Michael (Cancers, 2021)
Chimeric antigen receptor T (CAR-T) cell therapy has proven to be very effective in patients with relapsed/refractory acute lymphoblastic leukemia (ALL) and non-Hodgkin lymphoma (NHL). However, infections—related either due to lymphodepletion or the CAR-T cell therapy itself—can result in severe and potentially life-threatening complications, while side effects such as cytokine release syndrome (CRS) might complicate differential diagnosis. Sixty-seven dosings of CAR-T cells in sixty adult patients with NHL (85%) and ALL (15%) receiving CAR-T cell therapy were assessed for infectious complications. Almost two-thirds of patients (61%) developed fever following lymphodepletion and CAR-T cell dosing. Microbiological or radiological findings were observed in 25% of all cases (bacterial 12%, viral 5%, fungal 8%). Inpatient infections were associated with more lines of therapy and more severe CRS. However, overall serious complications were rare after CAR-T therapy, with one patient dying of infection. Pathogen detection after inpatient stay was infrequent and mostly occurred in the first 90 days after dosing. Infections in CAR-T cell treated patents are common. Fast and suitable identification and treatment are crucial in these heavily pretreated and immunocompromised patients. In most cases infectious complications are manageable. Nonetheless, standardized anti-infective prophylaxis and supportive therapy are mandatory to reduce morbidity and mortality in CAR-T cell therapy.